To be a butterfly a study of protective strategies. - Center for Humanities, Inc. (Ltd. : Oxford Scientific Films, 1986)
Tracks the life cycle of the butterfly, emphasizing defence mechanisms at both the caterpillar and butterfly stages. Enumerates functions of butterfly wing - for good gathering, courtship, defence.
Keywords: Butterflies -- Australia; Caterpillars -- Australia